Clinicopathological Evaluation of Extragonadal Germ Cell Tumors - A Retrospective Study from a Regional Cancer Center in India - Ramamurthy, Sindhu; S Kaushik, Prakruthi; Mysore Narayana, Suma; Amirtham, Usha; Babu M.C, Suresh; Patil, Akamahadevi; Gopal, Champaka; Patil Okaly, Geeta V; Nargund, Ashwini (Asian Pacific Journal of Cancer Care, 2024)
Background and objective: Extragonadal germ cell tumors (EGGCTs) are tumors that arise outside the gonads. Their biological behavior and prognosis differ from their gonadal counterparts. This study aimed to analyze the histological subtypes, outcomes, and prognoses of EGGCTs in patients of various age groups. Material and Methods: This retrospective analysis was conducted on all patients diagnosed with EGGCTs between January 2017 and December 2019 at a regional cancer center in India. Results: The study included 61 cases of EGGCTs, divided into three age groups: neonatal (birth to six months), prepubertal (more than six months to 12 years), and postpubertal (over 12 years). The prepubertal group was the most frequently affected (44.2%). The age range was from birth to 45 years, with a male-to-female ratio of 1:1.03. The most common primary site was the sacrococcyx (36%), followed by the mediastinum (31.1%). The most prevalent histological subtype was mature teratoma (39.3%), followed by yolk sac tumor (YST) (18%), mixed germ cell tumor (18%), immature teratoma (14.7%), and germinoma (9.8%). Four cases of teratoma exhibited somatic malignancies. The tumor stage distribution was 48 stage I, 8 stage II, and 2 stage III. Statistical analysis revealed a significant association between age group and primary site (p=0.004), histological type (p=0.002), and clinical stage (p=0.034). With a median follow-up of 30 months, an overall survival (OS) rate of 93.2% and an event-free survival (EFS) rate of 90.4% were observed across all age groups. OS rates were 100% (neonatal), 96% (prepubertal), and 88.0% (postpubertal), showing a declining trend with increasing age (p=0.324). Significant prognostic factors for OS included histological subtype (mixed germ cell tumors and teratomas with somatic malignancies had reduced OS) and stage (I vs II and III). Stage was the only significant prognostic factor for EFS (P<0.0001). Conclusion: This study highlights the clinicopathological characteristics, prognostic parameters, and outcomes of EGGCTs. It emphasizes the importance of detailed pathological reporting for these lesions and the need for comprehensive management strategies tailored to specific age groups and histological subtypes.